1992
DOI: 10.1007/bf01321723
|View full text |Cite
|
Sign up to set email alerts
|

Using lay health workers: Case study of a community-based prenatal intervention

Abstract: This article reports on the design and implementation of a prenatal outreach and education intervention for low income, Hispanic women living in three migrant and seasonal farmworker communities in Arizona. The program included three major elements: a Spanish language prenatal curriculum; a group of mature Hispanic women recruited from the target communities and trained as "Comienzo Sano" (healthy beginning) Promotoras (health promoters), and the organization of a support network of local health professionals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 19 publications
(1 reference statement)
1
37
0
Order By: Relevance
“…The CLS program sought to modify factors influencing Pap testing through a culturally competent program delivered by lay health workers (LHWs) to Hispanic women 50 and older in farmworker communities. The LHW model is based on peer health education in which community members deliver educational messages and connect women with health care resources [24–32] and has been effectively used to increase access to health services including Pap test screening [27,30,3337]. The CLS program used Community Guide recommended approaches including one-on-one education and small media strategies for increasing screening [38].…”
Section: Research-tested Intervention Approaches In Hispanic Communitiesmentioning
confidence: 99%
“…The CLS program sought to modify factors influencing Pap testing through a culturally competent program delivered by lay health workers (LHWs) to Hispanic women 50 and older in farmworker communities. The LHW model is based on peer health education in which community members deliver educational messages and connect women with health care resources [24–32] and has been effectively used to increase access to health services including Pap test screening [27,30,3337]. The CLS program used Community Guide recommended approaches including one-on-one education and small media strategies for increasing screening [38].…”
Section: Research-tested Intervention Approaches In Hispanic Communitiesmentioning
confidence: 99%
“…11 12 In general, the literature indicates that promotores can increase access to the target audience and improve accessibility to health care resources. 12 13 The approach has been applied in cancer and cardiovascular disease risk reduction programmes for Latinos with promising results, [14][15][16] although rigorous evaluations are rare.…”
Section: Promotor Approach Recruitment and Trainingmentioning
confidence: 99%
“…Indeed, interest in promotores programs has been particularly prominent in low income countries in which the formal health system has failed to provide adequate care for low-income groups (Hadley, Cunningham, & Hargraves, 2006). Studies indicate that promotores have been shown to be effective in reaching minority populations, particularly those with barriers to accessing health care resources (Woodruff, Talavera, & Elder, 2002) (Lewin, 2005; Meister, Warrick, de Zapien, & Wood, 1992; Mock et al, 2007). The Institute of Medicine report “Unequal Treatment” recommends community health workers to improve use of preventive and primary care services (Lewin, 2005; Lewin, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%